Faktor-Faktor yang Mempengaruhi Persepsi Etika Mahasiswa Akuntansi dengan Love of Money sebagai Variabel Intervening - Fitri Arshinta; Mohammad Djasuli; Yuni Rimawati (Jurnal Keuangan dan Perbankan, 2017)
Competition in globalization that is very firm gives impact on every class to maintain their position. As the prospective accountant, students not only know well about the theory but also etiquette in enduring the profession to decrease the digressing in the future. This thesis is aimed to evaluate empirically some factors that influence the ethical perception of accountancy students with “love of money” as the intervening variable. Independent variables are gender, level of education, age, economic socials status, and ethnic background. Intervene variable is a love of money and the dependent variable is ethical perception. This thesis uses the primary data that is collected by the questioner for some respondents that are still the accountancy students. Population in this thesis is all of the accountancy students in the state university (PTN) in Suramadu (Surabaya-Madura), and in choosing the population, this thesis uses the criteria as a sample and called as “purposive sample”. The sample that has been collected from the questioner is 95 respondents. The technique for analyzing the data is SEM (Structural Equation Modeling). Moreover, the tabulation of the data uses the program SmartPLSversion 2.0. According to the result of the analysis in this thesis shows that gender, level of education, age, and ethnic background do not influence significantly toward the “love of money”, yet economic status social influences significantly toward the “love of money”. However the level of education, age, economic status social, and ethnic background do not influence significantly toward the ethical perception, yet age influences significantly toward the ethical perception. “love of money” does not influence significantly as the intervening variable as well as.